Prevention of cisplatin-induced ototoxicity in children and adolescents with cancer: a clinical practice guideline. (February 2020) - Freyer, David R; Brock, Penelope R; Chang, Kay W; Dupuis, L Lee; Epelman, Sidnei; Knight, Kristin; Mills, Denise; Phillips, Robert; Potter, Emma; Risby, Demie; Simpkin, Philippa; Sullivan, Michael; et al.
Summary: Despite ototoxicity being a prevalent consequence of cisplatin chemotherapy, little guidance exists on interventions to prevent this permanent and progressive adverse event. To develop a clinical practice guideline for the prevention of cisplatin-induced ototoxicity in children and adolescents with cancer, we convened an international, multidisciplinary panel of experts and patient advocates to update a systematic review of randomised trials for the prevention of cisplatin-induced ototoxicity. The systematic review identified 27 eligible adult and paediatric trials that evaluated amifostine, sodium diethyldithiocarbamate or disulfiram, systemic sodium thiosulfate, intratympanic therapies, and cisplatin infusion duration. Regarding systemic sodium thiosulfate, the panel made a strong recommendation for administration in non-metastatic hepatoblastoma, a weak recommendation for administration in other non-metastatic cancers, and a weak recommendation against its routine use in metastatic cancers. Amifostine, sodium diethyldithiocarbamate, and intratympanic therapy should not be routinely used. Cisplatin infusion duration should not be altered as a means to reduce ototoxicity. Further research to determine the safety of sodium thiosulfate in patients with metastatic cancer is encouraged.